Blueprints 1 - Keith S. Folse (Houghton Mifflin, 2003)
Offers a combination of instruction in the rhetorical processes as well as paraphrasing, summarizing, and synthesizing. This title features multi-layered approaches that helps students develop good writing habits and avoid the pitfalls of plagiarism. It provides students various opportunities to write at the sentence, paragraph, and essay levels